(untitled) (Research, Society and Development, 2020)
It is an experience related to the acquisition of goods in the Public Administration, and itsobjective is to demonstrate the process of purchasing public goods through Adherence to the Price Registration Act / “Carona” and the evaluations of the products purchased. The research method used was descriptive/exploratory with a qualitative approach, defined as an experience report, that took place at Federal University Restaurant, in Niterói - Rio de Janeiro, Brazil, from November/2017 to April/2018. It pointed out the need to replace four industrial cauldrons, since those existing in the unit presented a risk to the safety of workers, having been chosen the “Carona” due to the “promised” speed for this bidding procedure and the urgent need for acquisition. However, upon delivery of the goods, the nutritionist found the equipment to be non-conforming, culminating in its return, and the company was granted the right to ample defense and expression of interest in solving the problem, and a commitment was made to redo the equipment, as described on the Edict. The final installation of the cauldrons took more than five months, causing frustration with the speed of the “Carona” due to the contractual default of bidder. Public Procurement encompasses a multiprofessional reality and broadly involves the health area, even though this experience has been carried out in the nutrition sector. This report intends to offer subsidies for new studies, and provide reflection of other professionals, regarding the need for effective skills to act in public contracts.